Topical enzyme-replacement therapy restores transglutaminase 1 activity and corrects architecture of transglutaminase-1-deficient skin grafts - Aufenvenne, Karin; Larcher, Fernando; Haußer-Siller, Ingrid; Duarte, Blanca; Oji, Vinzenz; Nikolenko, Heike; Del Rio, Marcela; Dathe, Margitta; Traupe, Heiko (The American journal of human genetics, 2013)
Transglutaminase-1 (TG1)-deficient autosomal-recessive congenital ichthyosis (ARCI) is a rare and severe genetic skin disease caused by mutations in TGM1. It is characterized by collodion babies at birth, dramatically increased transepidermal water loss (TEWL), and lifelong pronounced scaling. The disease has a tremendous burden, including the problem of stigmatization. Currently, no therapy targeting the molecular cause is available, and the therapeutic situation is deplorable. In this study, we developed the basis for a causative therapy aiming at the delivery of the enzyme to the inner site of the keratinocytes’ plasma membrane. We prepared sterically stabilized liposomes with encapsulated recombinant human TG1 (rhTG1) and equipped with a highly cationic lipopeptide vector to mediate cellular uptake. The liposomes overcame the problems of insufficient cutaneous delivery and membrane penetration and provided excellent availability and activity of rhTG1 in primary keratinocytes. To demonstrate the general feasibility of this therapeutic approach in a humanized context, we used a skin-humanized mouse model. Treatment with rhTG1 liposomes resulted in considerable improvement of the ichthyosis phenotype and in normalization of the regenerated ARCI skin: in situ monitoring showed a restoration of TG1 activity, and cholesterol clefts vanished ultrastructurally. Measurement of TEWL revealed a restoration of epidermal barrier function. We regard this aspect as a major advance over available nonspecific approaches making use of, for example, retinoid creams. We conclude that this topical approach is a promising strategy for restoring epidermal integrity and barrier function and provides a causal cure for individuals with TG1 deficiency.